Membrane Mediated Antimicrobial and Antitumor Activity of Cathelicidin 6: Structural Insights from Molecular Dynamics Simulation on Multi-Microsecond Scale - Sahoo, Bikash Ranjan; Fujiwara, Toshimichi (PLOS ONE, 2016)
The cathelicidin derived bovine antimicrobial peptide BMAP27 exhibits an effective microbicidal activity and moderate cytotoxicity towards erythrocytes. Irrespective of its therapeutic and multidimensional potentiality, the structural studies are still elusive. Moreover, the mechanism of BMAP27 mediated pore formation in heterogeneous lipid membrane systems is poorly explored. Here, we studied the effect of BMAP27 in model cell-membrane systems such as zwitterionic, anionic, thymocytes-like (TLM) and leukemia-like membranes (LLM) by performing molecular dynamics (MD) simulation longer than 100 μs. All-atom MD studies revealed a stable helical conformation in the presence of anionic lipids, however, significant loss of helicity was identified in TLM and zwitterionic systems. A peptide tilt ( 45˚) and central kink (at residue F10) was found in anionic and LLM models, respectively, with an average membrane penetration of < 0.5 nm. Coarse-grained (CG) MD analysis on a multi-μs scale shed light on the membrane-dependent peptide and lipid organization. Stable micelle and end-to-end like oligomers were formed in zwitterionic and TLM models, respectively. In contrast, unstable oligomer formation and monomeric BMAP27 penetration were observed in anionic and LLM systems with selective anionic lipid aggregation (in LLM). Peptide penetration up to 1.5 nm was observed in CG-MD systems with the BMAP27 C-terminal oriented towards the bilayer core. Structural inspection suggested membrane penetration by micelle/end-to-end like peptide oligomers (carpet-model like) in the zwitterionic/TLM systems, and transmembrane-mode (toroidal-pore like) in the anionic/LLM systems, respectively. Structural insights and energetic interpretation in BMAP27 mutant highlighted the role of F10 and hydrophobic residues in mediating a membrane-specific peptide interaction. Free energy profiling showed a favorable (-4.58 kcal mol-1 for LLM) and unfavorable (+0.17 kcal mol-1 for TLM) peptide insertion in anionic and neutral systems, respectively. This determination can be exploited to regulate cell-specific BMAP27 cytotoxicity for the development of potential drugs and antibiotics.